Enucleated bone marrow-derived mesenchymal stromal cells regulate immune microenvironment and promote testosterone production through efferocytosis - Lu Sun; Jiayu Huang; Xuezi Wang; Peng Huang; Baolin Dong; Zehang Liang; Jiahong Wu; Jiancheng Wang (Reproductive Biology and Endocrinology)
Abstract Background Testosterone deficiency (TD) occurs most frequently in older men and can cause many health problems. Testosterone replacement therapy (TRT) is widely used to treat TD, but this regimen can lead to a series of side effects. Stem cell therapy has been wildly studied in vitro. However, due to the multidirectional differentiation potential and heterogeneity of stem cells, it is difficult to achieve the good efficiency and reproducibility in basic research and clinical applications. This study aims to identify a new strategy for the treatment of TD. Methods Bone marrow-derived mesenchymal stromal cells (BMSCs) were enucleated by Ficoll density gradient centrifugation. The organelles and cellular functions of enucleated BMSCs were analyzed by immunofluorescence staining and flow cytometry. Extracellular vesicles (EVs) were isolated by ultracentrifugation and characterized. For the animal studies, enucleated BMSCs were labelled with Mitotracker and injected into ethane dimethanesulfone (EDS)-treated rats. Testosterone production and spermatogenesis were detected at different time points through various tests. To determine the mechanism of efferocytosis, we analysed the number of macrophages by immunofluorescence staining and quantitative real-time polymerase chain reaction (qRT-PCR). Results The injection of enucleated BMSCs (Cargocytes) into the testes of EDS-treated rats restored the levels of serum testosterone, increased the number of Leydig cells (LCs), and improved spermatogenesis. We found that enucleated BMSCs underwent apoptosis earlier than BMSCs did. Subsequently, testicular interstitial macrophages phagocytosed apoptotic enucleated BMSCs through efferocytosis. Efferocytosis promoted macrophage polarization from the M1 to the M2 phenotype, reduced the expression of proinflammatory cytokines, and decreased the levels of inflammation and oxidative stress. Conclusions In summary, this study pioneered the application of stromal cell enucleation technology to repair tissue damage in the reproductive system, explored the potential of cell burial in the treatment of reproductive system diseases and provided a new approach for the clinical treatment of male infertility.